2007
DOI: 10.1590/s0104-56872007000300007
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho de adultos brasileiros normais na prova semântica: efeito da escolaridade

Abstract: Background: modern concepts on the neuropsychological bases of language consider that its network has a direct relation with the support systems such as attention and memory. Semantic memory constitutes the basis of knowledge, communication and learning. Semantic knowledge is consolidated with the exposure to information and the possibility to integrate information. Thus, aging and literacy can be associated to semantic knowledge. Aim: to analyze in normal Brazilian adults the interference of literacy through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Saygin et al, dedicated to study linguistic and nonlinguistic stimuli,and found that the subjects' performance was demoted and suggested that key areas for production are also related to the comprehension 12 .It was observed in another study that the temporal lobe, the temporal junction frontal-parietal and posterior areas are involved in naming and understanding tasks 13 . Other authors argue that the reconstruction and improvement of production and comprehension of language (linguistic factors and non-linguistic) can be related 14,15 . This study did not use additional language measures for testing the lexical-semantic system.…”
Section: Discussionmentioning
confidence: 99%
“…Saygin et al, dedicated to study linguistic and nonlinguistic stimuli,and found that the subjects' performance was demoted and suggested that key areas for production are also related to the comprehension 12 .It was observed in another study that the temporal lobe, the temporal junction frontal-parietal and posterior areas are involved in naming and understanding tasks 13 . Other authors argue that the reconstruction and improvement of production and comprehension of language (linguistic factors and non-linguistic) can be related 14,15 . This study did not use additional language measures for testing the lexical-semantic system.…”
Section: Discussionmentioning
confidence: 99%
“…The study of Machado et al (2007) had as a purpose to analyze in normal Brazilian adults the interference of literacy through the performance in a semantic test. The study concluded that it was possible to observe that low literacy levels had a negative influence on the performance presented in tasks involving semantic knowledge, judgment of traces and naming, particularly when involving animated pictures.…”
Section: Claudia Regina Furquim De Andrade Professora Titular Departamentioning
confidence: 99%
“…Como ilustração, a educação é talvez uma das variáveis sociodemográficas com maior representatividade na pesquisa da interação destes fatores com o desempenho neuropsicológico (Ostrosky-Solís, Ramírez, & Ardila, 2004). Os estudos investigam as funções cognitivas como atenção (Rosselli, Tappen, Williams, & Salvatierra, 2006), percepção, linguagem Estudos de Psicologia, 17(2), maio-agosto/2012, 215-222 (Machado, Correia, & Mansur, 2007) e memória de trabalho (Talarico, Caramelli, Nitrini, & Chaves, 2007), entre outros, na qual uma ou mais destas variáveis parecem apresentar um relevante papel nos referidos processamentos cognitivos.…”
Section: Introductionunclassified